Consequences of Prematurity on Cortisol Regulation and Adjustment Difficulties: A 9-Year Longitudinal Study - Auriana Urfer; Hélène Turpin; Nevena Dimitrova; Ayala Borghini; Kerstin Jessica Plessen; Mathilde Morisod Harari; Sébastien Urben (MDPI AG, 2021)
A preterm birth represents a stressful event having potentially negative long-term consequences. Thirty-three children born preterm (<33 weeks gestational age) and eleven full-term children participated in a nine-year longitudinal study. Perinatal Risk Inventory (PERI) was used at birth to assess the perinatal stress. Salivary cortisol, collected four times a day over two consecutive days, was measured with radioimmunoassay technique at six months and nine years to assess the hypothalamic-pituitary-adrenal (HPA) axis. Mothers reported post-traumatic symptoms on a self-report questionnaire 12 months after their child's birth and children's adjustment problems at 9 years of child age on the Child Behavior Checklist. Results showed a significant difference in cortisol regulation at nine years between preterm and full-term children but no differences in adjustment problems. Whereas biological factors (i.e., PERI, cortisol regulation at six months) explained cortisol at nine years, maternal post-traumatic symptoms were predictive of adjustment problems in their child. In conclusion, very preterm birth has some long-term consequences on the HPA-axis regulation at nine years. Although cortisol regulation is mostly influenced by biological factors, the presence of maternal post-traumatic symptoms predicts the manifestation of adjustment problems in both groups. This shows the importance of maternal psychological well-being for child development. Further research is needed to understand the exact consequences of premature birth on cortisol regulation and the implication for the child's development and health.